The functional Mi-2/Foxo complex targets PGRP-SC2 for the Drosophila immune defense against bacterial infection - Zheng, Xianrui; Ali, Umar; Jin, Yiheng; Ding, Erwen; Zhu, Yangyang; Usama, Muhammad; Cai, Qingshuang; Ji, Shanming (Frontiers in Immunology, 2025)
Innate immunity is orchestrated by an array of conserved signaling pathways and transcriptional regulators. While Forkhead box O (Foxo) has emerged as a pivotal transcription factor in regulating immune homeostasis, its interaction with chromatin remodeling machinery remains poorly defined. Here, we identify the chromatin remodeler Mi-2 as a crucial component of the Drosophila antibacterial immune defense. Silencing of Mi-2 abrogates the induction of antimicrobial peptides in adult flies and leads to reduced host survival following systemic bacterial challenge. Co-immunoprecipitation assays demonstrate a physical interaction between endogenous Mi-2 and Foxo in the Drosophila fat body. Of interest, Foxo silencing phenocopies Mi-2 knockdown, suggesting a functional interdependence between the two factors. Mechanistically, the Mi-2/Foxo functional complex binds to the 5’ flanking region of Peptidoglycan recognition protein SC2 (PGRP-SC2), a negative regulator of the immune deficiency (IMD) signaling pathway, to prevent PGRP-SC2 expression. Genetic epistasis experiments support a hierarchical relationship, with PGRP-SC2 acting downstream of Mi-2/Foxo. Collectively, our findings uncover a previously uncharacterized chromatin-based regulatory mechanism whereby Mi-2 collaborates with Foxo to mediate the antibacterial immune response in Drosophila.